2022
DOI: 10.1039/d1sm01655e
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide-based composite organohydrogels with high strength and low temperature resistance for strain sensors

Abstract: In the recent years, a rapid development of the polymeric hydrogel-based sensors has been witnessed. However, conventional hydrogels often exhibit poor mechanical properties. Additionally, the use of these sensors at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This surface is rougher than typical, which helps to increase the surface area. By boosting ion transport and polymer chain mobility, it will improve the self-healing ability of hydrogels ( Khan et al, 2021d ; Zhao et al, 2022 ). It was also observed that increasing TEOS amount caused GO to cause more GO clustering at 300 µm as presented with red arrows.…”
Section: Resultsmentioning
confidence: 99%
“…This surface is rougher than typical, which helps to increase the surface area. By boosting ion transport and polymer chain mobility, it will improve the self-healing ability of hydrogels ( Khan et al, 2021d ; Zhao et al, 2022 ). It was also observed that increasing TEOS amount caused GO to cause more GO clustering at 300 µm as presented with red arrows.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, artificial intelligence has gradually been becoming a quite hot research area and is regarded as the core technology leading the fourth industrial revolution, which means that human labor can be replaced in principle by intelligent robots. Flexible strain sensors can be integrated into machines as a sensing element for machine perception, and human-robot interaction [53,[210][211][212][213][214][215][216][217][218][219][220], which is crucial for Industry 4.0. Recently, Zhao et al [54] reported a flexible thin-film e-skin composed of CNTs/PDMS composite film with layered structure and interdigital electrode.…”
Section: Human-machine Interactionmentioning
confidence: 99%
“…[3,4] The utility of these materials lies in their ability to potentially facilitate the creation of smart wearable skin-on devices for high precision, real-time biomechanical and vital signs measurements. [5,6] Past research on utilizing the electromechanical response of graphene networks has demonstrated composite materials in many forms; from mixed-phase solid films, [7][8][9] foams, [10][11][12] fibers, [13,14] fabrics, [15][16][17] gels, [18][19][20] to micro structured [21][22][23] and templated [17,24,25] heterostructures. The popularity of applying graphene nanocomposites lay in the cost efficiency associated with making nanosheets in the liquid phase and the cheap polymer materials applied to fabricate devices.…”
Section: Introductionmentioning
confidence: 99%